PEMODELAN SPASIOTEMPORAL PERSEBARAN LAHAN TERBANGUN DI DISTRIK KURIK, KABUPATEN MERAUKE - Agriarso Wahyu Septiawan, Agriarso Wahyu Septiawan; Mujiati, Mujiati; Dewi Ana Rusim, Dewi Ana Rusim (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2026)
This study examines the spatiotemporal patterns of built-up land changes in Kurik District, Merauke Regency, from 2015 to 2024. Utilizing Landsat 8 and 9 satellite imagery alongside supervised classification and Change Detection Analysis methods, the research aims to comprehensively model spatial and temporal dynamics of land cover transformation. Internal and external validations yielded classification accuracies exceeding 90% with kappa indices above 0.80, despite challenges arising from spectral similarities between built-up areas and low-density vegetation. The analysis reveals a significant increase in built-up land area driven by population growth and infrastructure expansion, particularly after 2020. High-density vegetation remains dominant but experienced decline due to forest degradation, followed by natural succession recovery. The distribution of built-up land varies across villages, reflecting heterogeneous development pressures and socio-economic dynamics. This study underscores the necessity of spatial planning management based on geographic information systems to balance development needs with sustainable agricultural land conservation. Limitations related to spatial resolution and field data present challenges for future research. Methodologically, the study offers valuable contributions to spatiotemporal modeling supporting sustainable agrarian regional planning in Papua and comparable areas.